2001
DOI: 10.1212/wnl.57.5.768
|View full text |Cite
|
Sign up to set email alerts
|

Individual semicircular canal function in superior and inferior vestibular neuritis

Abstract: Vestibular neuritis can affect the superior and inferior vestibular nerves together or can selectively affect the superior vestibular nerve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
148
0
19

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(178 citation statements)
references
References 19 publications
11
148
0
19
Order By: Relevance
“…Only 1/3 of the patients of Hong et al showed abnormal cervical VEMPs, suggesting that visual vertical measurements may be superior to cervical VEMPS in identifying vestibular neuritis. Since in most patients vestibular neuritis spares the inferior division of the vestibular nerve (Aw, Fetter, 2001;Fetter and Dichgans, 1996;Schmid-Priscoveanu, Straumann, 1999), a higher sensitivity for utricular tests, such as vibration induced oVEMP or the visual vertical, than of saccular tests, such as cervical VEMPs evoked by air conducted sound, is expected. Indeed, it has recently been reported that in a large sample of patients with unilateral vestibular loss, the SVV during eccentric rotation in patients was significantly more asymmetric than cervical VEMPS (Schonfeld, Helling, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Only 1/3 of the patients of Hong et al showed abnormal cervical VEMPs, suggesting that visual vertical measurements may be superior to cervical VEMPS in identifying vestibular neuritis. Since in most patients vestibular neuritis spares the inferior division of the vestibular nerve (Aw, Fetter, 2001;Fetter and Dichgans, 1996;Schmid-Priscoveanu, Straumann, 1999), a higher sensitivity for utricular tests, such as vibration induced oVEMP or the visual vertical, than of saccular tests, such as cervical VEMPs evoked by air conducted sound, is expected. Indeed, it has recently been reported that in a large sample of patients with unilateral vestibular loss, the SVV during eccentric rotation in patients was significantly more asymmetric than cervical VEMPS (Schonfeld, Helling, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Maximum errors were <2%. The search coil signals were computed in three dimensions in rotation vectors and Euler angles as position and velocity in space/head fixed coordinates (Aw et al 2001Fahey et al 2008;Weber et al 2008). …”
Section: Head and Eye Movement Recordings And Analysismentioning
confidence: 99%
“…We characterized the vestibular function and its conduction pathways with mechanically and electrically evoked vestibular stimuli. We used the HIT to assess individual semicircular canal function (Aw et al 2001); air-conducted click evoked ocular and cervical VEMPs to assess the otolith functions (Taylor et al 2011) and EVS to examine the vestibular conduction pathway latency, and low and high frequency response of the vestibular system . Ocular motor abnormalities were investigated with volitional horizontal and vertical saccades, vergence, and smooth pursuit (Fahey et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it can be inferred by testing the subjective visual horizontal, an easy test that can be done in any clinical neurophysiology department. 23 In some patients the disorder only affects the superior vestibular nerve and spares the inferior division of the vestibular nerve 24 so that the patient with vestibular neuritis is able to develop BPPV, presumably as a consequence of otoconia being shed from the utricle into the duct of the posterior semicircular canal.…”
Section: Acute Vestibular Neuritismentioning
confidence: 99%